Obstacles Faced by College Students in Solving Probability Word Problems - Mardiana Yusuf; Suzieleez Syrene Abdul Rahim; Leong Kwan Eu (Jurnal Pendidikan Matematika, 2021)
There are many difficulties that can be identified when students solve mathematic problems especially in solving probability word problems. This study was conducted to identify the major obstacles faced by matriculation college students while solving the probability of an event word problems. Seven college students were the sample for this case study. Clinical interviews are used as a data collection. This data collection technique was selected based on the researcher’s observation on the participants as they answered the probability word problem task. The task was given during the interview session. Semi structured interviews are used to obtain in depth information. Think-aloud analysis involves observations leading to individual behaviours in the oral or nonverbal form of participants and the researcher’s field notes. Participants were found to have difficulty interpreting probabilities. There are three categories of difficulties that have been identified, namely not knowing the meaning of the word, not knowing the nature of the probability and not being able to identify the goal of the probability word problem.